Resveratrol and Pterostilbene, Two Analogue Phenolic Compounds, Affect Aquaglyceroporin Expression in a Different Manner in Adipose Tissue - Saioa Gómez-Zorita (International Journal of Molecular Sciences, 2018)
Aquaglyceroporins (AQPs) are transmembrane channels that mediate glycerol release and glycerol uptake. They are involved in fat metabolism, with implications in obesity. The aim was to determine whether the administration of resveratrol and pterostilbene during the six weeks of the experimental period would modify AQPs expression in white and brown adipose tissues from Wistar rats fed an obesogenic diet, and to establish a potential relationship with the delipidating properties of these compounds. Consequently, thirty-six rats were divided into four groups: (a) group fed a standard diet; and three more groups fed a high-fat high-sucrose diet: (b) high-fat high-sucrose group: (c) pterostilbene-treated group (30 mg/kg/d): (d) resveratrol-treated group (30 mg/kg/d). Epididymal, subcutaneous white adipose tissues and interscapular brown adipose tissue were dissected. AQPs gene expression (RT-PCR) and protein expression (western-blot) were measured. In white adipose tissue, pterostilbene reduced subcutaneous adipose tissue weight and prevented the decrease in AQP9 induced by obesogenic feeding, and thus glycerol uptake for triglyceride accumulation. Resveratrol reduced epididymal adipose tissue weight and avoided the decrease in AQPs related to glycerol release induced by high-fat high-sucrose feeding, suggesting the involvement of lipolysis in its body-fat lowering effect. Regarding brown adipose tissue, AQP7 seemed not to be involved in the previously reported thermogenic activity of both phenolic compounds.